2023
DOI: 10.1088/1361-6528/ad0d21
|View full text |Cite
|
Sign up to set email alerts
|

A simple strategy to obtain graphitic carbon nitride modified TiO2 layer for efficient perovskite solar cells

Yanru Guo,
Dandan Zhao,
Man Yu
et al.

Abstract: The power conversion efficiency (PCE) of perovskite solar cells (PSCs) can be improved through the concurrent strategies of enhancing charge transfer and passivating defects. Graphite carbon nitride (g-C3N4) has been demonstrated as a promising modifier for optimizing energy level alignment and reducing defect density in PSCs. However, its preparation process can be complicated. A simple one-step calcination approach was used in this study to prepare g-C3N4-modified TiO2 via the incorporation of urea into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…21−23 Apart from the detrimental defects, the imperfect band alignment across the interface usually disturbs charge carrier diffusion, eventually resulting in low V OC and PCE. 24,25 Furthermore, the massive defects and pinholes in CsPbI 2 Br perovskite films could accelerate ion migration and allow moisture to unscrupulously immerse into the perovskite film, resulting in undesirable stability for the devices. 26 To obtain highly efficient and stable CsPbI 2 Br PSCs, various approaches have been applied to prepare high-quality perovskite films and stabilize the lattice structure, such as dopant engineering, 27,28 dimension regulation, 29 and interface engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21−23 Apart from the detrimental defects, the imperfect band alignment across the interface usually disturbs charge carrier diffusion, eventually resulting in low V OC and PCE. 24,25 Furthermore, the massive defects and pinholes in CsPbI 2 Br perovskite films could accelerate ion migration and allow moisture to unscrupulously immerse into the perovskite film, resulting in undesirable stability for the devices. 26 To obtain highly efficient and stable CsPbI 2 Br PSCs, various approaches have been applied to prepare high-quality perovskite films and stabilize the lattice structure, such as dopant engineering, 27,28 dimension regulation, 29 and interface engineering.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the PCE of CsPbI 2 Br-based PSCs is still far from its theoretical limitations, which were mainly attributed to the poor quality of the perovskite film . As is known to all, the CsPbI 2 Br perovskite films are always prepared by solution processing, and they contain substantial disordered structures, such as grain boundary defects and crystallographic defects at the surface. , Previous studies have demonstrated that the inferior defects derived from solution processing would cause severe nonradiative recombination of photoinduced charges. Apart from the detrimental defects, the imperfect band alignment across the interface usually disturbs charge carrier diffusion, eventually resulting in low V OC and PCE. , Furthermore, the massive defects and pinholes in CsPbI 2 Br perovskite films could accelerate ion migration and allow moisture to unscrupulously immerse into the perovskite film, resulting in undesirable stability for the devices . To obtain highly efficient and stable CsPbI 2 Br PSCs, various approaches have been applied to prepare high-quality perovskite films and stabilize the lattice structure, such as dopant engineering, , dimension regulation, and interface engineering. Among all strategies, surface modification has been regarded as a convenient and effective way to eliminate the numerous defects at surface and grain boundaries and strengthen the stability of perovskite films .…”
Section: Introductionmentioning
confidence: 99%